Improving Student Learning Outcomes in Indonesia Material Writing Announcement With Model Student Teams-Achievement Learning Division (Stad) in Class Iv SD Negeri 21 / III Koto Patah Kerinci District - Rama Mulia Putra; Taufina Taufik (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to determine the effect of Indonesian language learning by using the Student Teams-Achievement Division (STAD) learning model on class student IV learning outcomes. This research was conducted at SD N 21 / III Koto Patah, Kerinci Regency. The methodology used in this study is Classroom Action Research (CAR). The research phase consists of four stages, namely : planning planning stage, implementation stage, observation stage and reflection stage. The results of this study indicate an increase in students' Indonesian learning outcomes, in the first cycle experienced an increase of 10% from the previous learning outcomes, from 40% to 50% and in the second cycle increased by 30% from the first cycle, 50% to 80%.